Early implementation learnings on acceptability and feasibility of “V”: a multi-level PrEP intervention designed with and for adolescent girls and young women in Zimbabwe - Thenjiwe Sisimayi; Definate Nhamo; Kumbirai Chatora; Gwendoline Chapwanya; Tinovonga Mawoyo; Getrude Ncube; Cal Bruns; Emily L. Harris; Katharine D. Shelley (Health Research Policy and Systems, 2023)
Abstract Introduction Adolescent girls and young women (AGYW) remain disproportionately affected by HIV in Zimbabwe. Several HIV prevention options are available, including oral tenofovir-based pre‐exposure prophylaxis (PrEP), however AGYW face unique barriers to PrEP uptake and continuation and novel approaches are therefore needed to empower AGYW to use PrEP. The objective of this study was to characterize early learnings from implementing a multi-level intervention consisting of fashionable branding (including a “V Starter Kit”), service integration, and peer education and support throughout a young woman's journey using oral PrEP across four phases of implementation, from creating demand, preparing for PrEP, initiation of PrEP, and adherence to PrEP. Methods A mixed methods implementation research study was undertaken, including site observations and interviews to explore the acceptability of “V” and its relevance to target users, as well as the feasibility of integrating “V” with existing service delivery models. Interviews (n = 46) were conducted with healthcare workers, Brand Ambassadors, and young women purposively sampled from four implementation sites. Interview data was analyzed thematically using the framework method for qualitative data management and analysis. Project budgets and invoices were used to compile unit cost and procurement data for all “V” materials. Results “V” was acceptable to providers and young women due to attractive branding coupled with factual and thought-provoking messaging, establishing “a girl code” for discussing PrEP, and addressing a gap in communications materials. “V” was also feasible to integrate into routine service provision and outreach, alongside other services targeting AGYW. Cost for the “V” branded materials ranked most essential—FAQ insert, pill case, makeup bag, reminder sticker—were $7.61 per AGYW initiated on PrEP. Conclusion “V” is a novel approach that is an acceptable and feasible multi-level intervention to improve PrEP access, uptake, and continuation among AGYW, which works through empowering AGYW to take control of their HIV prevention needs. In considering “V” for scale up in Zimbabwe, higher volume procurement and a customized lighter package of “V” materials, while still retaining V’s core approach, should be explored.